1999
DOI: 10.1046/j.1365-3083.1999.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Immunoglobulin A Influences Its Receptor Binding

Abstract: Immunoglobulin A (IgA), which is heavily glycosylated, interacts with a variety of receptors, e.g. the asialoglycoprotein receptor (ASGP-R), which binds terminal galactose residues, and the Fcalpha receptor (FcalphaRI). It has thus been proposed that elevated serum levels of IgA in primary Sjögren's syndrome (pSS) are caused by its defective clearance. To test this hypothesis, we developed a method (based on sialyl transferases eluted from a hepatoma cell line) to increase the amount of sialic acid (SA) on IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Another study (49) that took both Fab and Fc glycosylation patterns in pSS patients into consideration reported that the proportion of sialylated IgA1 and IgA2 was increased in pSS patients compared with normal controls. This was postulated to decrease binding of IgA by immune receptors and result in altered clearance (50). We are currently evaluating as to whether our observations in pSS could be relevant in the context of other autoimmune diseases as well.…”
Section: Acquisition Of N-glycosylation Motifs On Frs Of Igg-producinmentioning
confidence: 95%
“…Another study (49) that took both Fab and Fc glycosylation patterns in pSS patients into consideration reported that the proportion of sialylated IgA1 and IgA2 was increased in pSS patients compared with normal controls. This was postulated to decrease binding of IgA by immune receptors and result in altered clearance (50). We are currently evaluating as to whether our observations in pSS could be relevant in the context of other autoimmune diseases as well.…”
Section: Acquisition Of N-glycosylation Motifs On Frs Of Igg-producinmentioning
confidence: 95%
“…Oversialylated IgA1 has a reduced affinity for ASPGR, which would reduce clearance by the liver and therefore lead to higher serum IgA1 levels [75]. Undersialylation and undergalactosylation lead to the aggregation of IgA1 in a hinge-specific manner [76], and undergalactosylation of IgA1 leads to increased adhesion to extracellular matrix proteins [77].…”
Section: Iga1 and Fcαri Aberrations Implicated In Iga Nephropathymentioning
confidence: 99%
“…This aberrant glycosylation of serum IgA1 could favor self-aggregation and formation of macromolecular complexes including the anti-IgA1 hinge peptide antibody [Coppo and Amore, 2004;Iwase et al, 1999;Kokubo et al, 2000]. Abnormally glycosylated IgA1 may also escape clearance by hepatic receptors for asialoglycoproteins [Basset et al, 1999]. Previous studies by us and others demonstrated that IgA1 with aberrant O-glycosylation had a higher binding capacity and stronger biologic effect on cultured human mesangial cells, leading to accumulation and/or persistence of IgA deposits within the mesangium Wang et al, 2004].…”
Section: Introductionmentioning
confidence: 99%